PENGARUH EKSTRAK KULIT JERUK PURUT (Citrus hystrix DC.) TERHADAPPENURUNANKADAR ASAM URAT MENCIT JANTAN (Mus musculusL.) YANG DIINDUKSI KALIUM BROMAT DAN SUMBANGANNYA PADA PEMBELAJARAN BIOLOGI SMA - Widyastuti Widyastuti; Lucia Maria Santoso; Riyanto Riyanto (Jurnal Pembelajaran Biologi: Kajian Biologi dan Pembelajarannya, 2017)
Abstract:This study aimed to determine the effect of lime peel extract to reduce uric acid levels of mice. The method used was experimental method with the complete randomized design using 24 male mice. This study consisted of four treatments and six repetitions. Treatment for the provision of distill water (control) and three dose levels consisting of 1,25 mg/10 gBB (P1),2,5 mg/10 gBB (P2), danÂ  5 mg/10 gBB (P3). The data were analyzed by doing the analysis of variance followed by computation test of Honestly Significant Difference (HSD).The obtained results showed that the average uric acid levels of this study were 1,8 mg/dL at a dose of 5 mg/10 gBB (P3) as the highest impact and 4 mg/dL at a dose of 1,25 mg/10 gBB (P1) as the lowest effect. Diversity analysis showed that the lime peel extract has the significant impact in reducing of uric acid levels of male mice. Honestly Significant Difference test (HSD) showed that there was a dose of lime peel extracts which is effective in reducing uric acid levels in mice; it was a dose of 5 mg/10 gBB. Based on the reduction of the uric acid levels, it could be concluded that lime peel extract could significantly reduce uric acid levels in mice. Information of the result in this study could be the input learning materials of Biology subject for the tenth senior high school students in the second semester on the Plantae Kingdom topic especially in competency 3.3 which explains about describing Divisioâ€™s characteristics in the Plantae Kingdom and its role for the life survival on earth. Keywords:Lime peel extract, uric acid levels, mice